Prison Riots in Nicaragua: Negotiating Co-Governance Amid Creative Violence and Public Secrecy. (March 2020) - Weegels, Julienne
In this article, I explore how prison riots, large critical incidents of a collective order, emerge, take place, and alter governance relations in place in the Nicaraguan prison system. Drawing on ethnographic research conducted with prisoners and former prisoners of two Nicaraguan prison facilities, I provide a prisoners' point of view on the political use of violence in prison, particularly during two large prison riots. While authorities often held that prison conditions combined with the "violent attitudes" of prisoners turned prisons into "powder kegs, " such an interpretation does not allow for an understanding of riots as embedded in prison governance structures and conveniently draws the attention away from underlying issues pertaining to the de facto sharing of power in prison in Nicaragua. I argue that by using what has been termed "creative violence, " prisoners attempt to break through the authorities' imposed regime of public secrecy and draw attention to these issues, forcing authorities to negotiate. Yet, even if riots then function as a catalyst for changes in co-governance arrangements, they do not appear to be geared at permanently damaging or annihilating the existing arrangements but rather at pressuring the authorities hard enough to make compromises and concessions as to the distribution of power in prison.